Toxinology in the proteomics era: a review on arachnid venom proteomics - Marchi,Filipi Calbaizer (2022)
Abstract The word venomics was coined to acknowledge the studies that use omics to investigate venom proteins and peptides. Venomics has evolved considerably over the last 20 years. The first works on scorpion or spider venomics were published in the early 2000’s. Such studies relied on peptide mass fingerprinting (PMF) to characterize venom complexity. After the introduction of new mass spectrometers with higher resolution, sensitivity and mass accuracy, and the next-generation nucleotide sequencing, the complexity of data reported in research on scorpion and spider venomics increased exponentially, which allowed more comprehensive studies. In the present review article, we covered key publications on scorpion venomics and spider venomics, presenting historical grounds and implemented technologies over the last years. The literature presented in this review was selected after searching the PubMed database using the terms “(scorpion venom) AND (proteome)” for scorpion venomics, and “(spider venom) AND (proteome)” for publications on spider venomics. We presented the key aspects related to proteomics in the covered papers including, but not restricted to, the employed proteomic strategy (i.e., PMF, two-dimensional gel electrophoresis, shotgun/bottom-up and/or top-down/peptidome), and the type of mass spectrometer used. Some conclusions can be drawn from the present study. For example, the scorpion genus Tityus is the most studied concerning venomics, followed by Centruroides; whereas for spiders the studied genera were found more equally distributed. Another interesting conclusion is the lack of high throughput studies on post-translational modifications (PTMs) of scorpion and spider proteins. In our opinion, PTMs should be more studied as they can modulate the activity of scorpion and spider toxins.